A novel process for the production of high-purity galactooligosaccharides (GOS) using consortium of microbes. Issue 3 (16th March 2017) - Saravanan, R.; Shubethar, Shajahan; Narayanan, S.; Jain, Manish; Lade, Shankar; Jadhav, Deepak; Maheswaran, P.; Avalakki, Uday K.; Dubey, Ashok Kumar
ABSTRACT: Galactooligosaccharides (GOS) are nondigestible dietary fibers which have a beneficial effect on human health by promoting the growth of probiotic bacteria in the gut. In addition, other health benefits have been reported from oligosaccharides consumption such as stimulation of intestinal mobility, colon cancer prevention, mineral absorption as well as protection against certain pathogenic bacterial infections. The goal of this research was to develop an efficient biotransformation system using a consortium of microbes for the production of ≥85% pure GOS and reusing the cell biomass in repeated cycles of biotransformation. Production of GOS by lactose transgalactosylation using whole cells of Sporobolomyces singularis MTCC 5491 as a source of β-galactosidase and monosaccharides utilization by yeast isolate (NUTIDY007) were studied. For increasing the purity of GOS, growth and bioconversion parameters on the transgalactosylation by the whole cells were investigated. Further, continuous production of GOS was studied in a reactor with microfiltration membrane system. A maximum GOS purity of 42% was achieved using single culture of S. singularis . Under optimized conditions, single culture of S. singularis produced a maximum of 56% pure GOS. Addition of second culture to the reaction mixture for utilization of glucose significantly increased the GOS purity from 56% to ≥85%. The product consisted of tri- to penta-galactooligosaccharides. Trisaccharides were the main component of the reaction mixture. A maximum productivity of 10.9 g/L/hr was obtained under the optimum conditions.